High-Frequency Trading around Large Institutional Orders - Vincent van Kervel; Albert J. Menkveld (Tinbergen Institute, 2017)
Liquidity suppliers lean against the wind. We analyze whether high-frequency traders (HFTs) lean against large institutional orders that execute through a series of child orders. The alternative is HFTs trading "with the wind," that is, in the same direction. We find that HFTs initially lean against these orders but eventually change direction and take position in the same direction for the most informed institutional orders. Our empirical findings are consistent with investors trading strategically on their information. When deciding trade intensity, they seem to trade off higher speculative profit against higher risk of detection by HFTs and being preyed on.
Keywords: G10; G14; G15; 330; High-frequency traders; institutional investors; trading patterns; transaction cost